Epidemiology of road traffic accidents and its associated factors among public transportation in Africa: systematic review and meta-analysis - Atalay, Yibeltal Assefa; Alemie, Bersufekad Wubie; Gelaw, Belete; Gelaw, Kelemu Abebe (Frontiers in Public Health, 2025)
IntroductionNowadays, Injuries, disabilities, and deaths due to road traffic accidents pose a major threat to public health worldwide. There was no meta-analysis study conducted in this area in Africa, hence the need for the study.ObjectivesThis review aimed to assess the pooled prevalence and associated factors of road traffic accidents among public transportation in Africa.MethodsThis systematic review and meta-analysis study was conducted in Africa according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Using Boolean logic operators and targeted keywords, we searched for publications on several electronic databases (Web of Science, PubMed, Google Scholar, African Journals Online (AJOL), and Science Direct). The degree of heterogeneity among the included studies, the 95% confidence interval, and the pooled prevalence were estimated using a random effects model.ResultsThis review included 45 studies with 15,968 participants. The overall estimated pooled prevalence of road traffic accident among public transportation in Africa was found to be 38.83% (95% CI: 33.54, 44.12). Meta-regression analysis indicated that sample size, publication year, country, study design, and sub-region had no significant impact on RTA prevalence. Based on a sub-group analysis by countries where the studies were conducted, the higher pooled prevalence of road traffic accidents was found in Congo at 67.90% (95% CI: 59.99, 75.81), while the lower pooled prevalence of road traffic accidents was in Libya at 15.80% (95% CI: 10.99, 20.61). Driving experience (AOR: 2.64, 95% CI: 1.70, 3.34), chewing Khat while driving (AOR = 4.69, CI: 2.80, 7.85), alcohol use (AOR = 2.72, CI: 1.49, 4.97), and receiving mobile phone calls while driving (AOR = 2.37, CI: 1.42, 3.95) were factors significantly associated with road traffic accidents.ConclusionIn conclusion, the pooled prevalence of road traffic accidents in Africa was found to be high. Therefore, we recommend that drivers have to strictly adhere to traffic regulations Moreover, It is recommended that policymakers and administrators ought to gain awareness of road traffic accidents and its risk factors to put existing road traffic accidents preventive and control measures into action.